1991
DOI: 10.2172/138284
|View full text |Cite
|
Sign up to set email alerts
|

Prototype heater test of the environment around a simulated waste package

Abstract: This paper presents selected results obtained during the 301 day duration of the Prototype Engineered Barrier System Field Test (PEBSFT) performed in G-Tunnel within the Nevada Test Site. The test described is a precursor to the Engineered Barrier Systems Field Tests (EBSFT) planned forlhe Exploratory Shaft Facility in Yucca Mountain. The EBSFT will consist of in situ tests of the geohydrologic and geochemical environment in the near field (within a few meters) of heaters emplaced in welded tuff to simulate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…• For the PEBSFT Ramirez et al, 1989 and1991b), moisture redistribution was observed using several boreholes spaced as closely as 0.5 m; the maximum radius of the dryout zone was determined to be approximately 0.7 m. The configuration of the dryout zone was circular and shifted downward relative to the heater axis. Evidence for shedding of condensate to the sides of the heater was observed.…”
Section: Discussionmentioning
confidence: 99%
“…• For the PEBSFT Ramirez et al, 1989 and1991b), moisture redistribution was observed using several boreholes spaced as closely as 0.5 m; the maximum radius of the dryout zone was determined to be approximately 0.7 m. The configuration of the dryout zone was circular and shifted downward relative to the heater axis. Evidence for shedding of condensate to the sides of the heater was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Heater tests in G-Tunnel at Ranier Mesa were performed by several investigators including Johnstone et al (1985) and Ramirez et al (1990). In at least one of those tests, thermally induced water movement was evidenced by water accumulation in the heater holes.…”
Section: Problem Statementmentioning
confidence: 99%